Soft Ultra-Orthodoxy: Revival Movement Activists, Synagogue Communities and the Mizrahi-Haredi Teshuva Movement in Israel - Leʾon, Nisim 1971- (2023)
This article offers an in-depth ethnographic and historical description of how an ethnic-religious revival movement has had an impact on religious life. The article will focus on the story of one of Israeli’s foremost religious revival movements—the Mizrahi-Haredi teshuva movement. We will look at the encounter between the Mizrahi-Haredi teshuva movement activists and Mizrahi synagogue congregations, and at the outcomes of that encounter on religious infrastructures, and on the activists’ religious agenda. The following questions will be addressed: How did the relationship between the activists and the synagogue congregations develop? What tensions arose and how did they turn a strict religious outlook into a soft religious approach? The article is based on many years of fieldwork in congregations exposed to the impact of the Mizrahi-Haredi teshuva movement in Israel. The fieldwork provided both a rich ethnographic inventory and an opportunity to describe a historical trend that illuminates the communal, authoritative, and gender models that originated with the encounter between the Mizrahi-Haredi teshuva movement activists and the local synagogue congregations.
Keywords: Israel; Teshuva; Mizrachim; Ultra-Orthodoxy; Ethnicity; religious revival movements